The Effect of Collaboration, Information Sharing and Digitalization Strategies on Logistics Performance with Logistic Capabilities as a Mediation Variable - Agit Audrie; Dadang Surjasa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the impact of collaboration, information sharing, and digitization strategies on logistics performance. This is mediated by the logistics function of companies operating in the supply chain industry. Researchers used primary data obtained from questionnaires that were included in the criteria for distributing questionnaires and designed to be answered by respondents which contained several statements. The sample size for this study is the index of each variable multiplied by 5. The number of indicators included in this survey is 5 times 26 indicators, the number of samples needed is 130 samples, and 135 responses are collected. Based on the results of the research, information sharing has a positive and significant impact on logistics capabilities, which is reflected by indicators explaining that information sharing has a positive impact on the organization both internally and externally. Logistics capability has a positive and significant influence on logistics performance which is reflected by various indicators in logistics capabilities which are supported by the quality of existing resources.